Interactions access. - Thrush, Emily Austin; Robert Baldwin Laurie Blass (McGraw-Hill, 1997)
English -- Listen -- Speak -- Skill
Keywords: Tiếng anh -Ngoại ngữ; Chứng chỉ A, B, C; Ngoại ngữ; A listening speaking book